The effect of mastectomy and radiotherapy for breast carcinoma soft tissues of the shooulder and its joint mobility among Egyptian patients - Saied, GM; Kamel, RM; Dessouki, NR (Tanzania Journal of Health Research, 2007)
No Abstract. Tanzania Health Research Bulletin Vol. 9(2) 2007: pp.121-125